Prevalence, correlates, and gender disparities related to eating disordered behaviors among health science students and healthcare practitioners in Lebanon: Findings of a national cross sectional study - Hoteit, Maha; Mohsen, Hala; Bookari, Khlood; Moussa, Ghadir; Jurdi, Najwa; Yazbeck, Nour (Frontiers in Nutrition, 2022)
Background The raised prevalence of eating disorders (ED) amongst health science students and health professionals is of mounting concern. This study aims to determine the prevalence and correlates of eating disorders risk amongst a sample of Lebanese health science students and healthcare practitioners of both genders. Methods This cross-sectional study enrolled a convenient sample of 1,000 participants (mean age: 23 ± 5.4; females: 74.9%) from faculties of health sciences, clinics, pharmacies, and hospitals. The validated Eating Attitudes Test (EAT-26) was used to screen for eating disorders. Anthropometric data were self-reported by respondents to assess their nutritional status. Results The risk of eating disorders was prevalent in 22.5% of participants. Females were at higher risk of ED compared to males p = 0.03. Eating disorders risk did not differ between students and practitioners (p = 0.3). The highest proportion of high-risk participants were students studying nutrition and practitioners (40.9%), outracing their counterparts in nursing (18.7%), medicine (17.8%), pharmacy (17.7%), and midwifery (4.9%) sciences (p = 0.02). Most high-risk participants had normal body weight (60.4%), and 28.9% were overweight (p = 0.001). Female gender, nutrition profession, and dieting were associated with increasing the odd of ED. Particularly, dieting increased the risk around five times. Further, each 3 participants over 10 were facing binge eating behavior. Conclusion This study uncovers an undervalued profession-related-health-disorder in Lebanese health science students and healthcare practitioners. Specific attention should be given to EDs in professional educational programmes across healthcare disciplines.